S?bre o valor do exame do sangue em gota esp?ssa colhida ?s primeiras horas da noite para inqu?ritos de Filariose de bancrofti (Publicado originalmente em 1949) - Deane, Maria Paumgartten (MS/SVS/Instituto Evandro Chagas, 2018)
To study Bancrofti?s filariasis in localities of the Amazon region of Brazil, surveys were being made through examination of thick smears of blood taken between 7:30 and 9:30 p.m. and stained by Giemsa?s. Time of collection being much earlier than the period of maximum microfilaraemia, and the quantity of blood examined quite small (about 20cumm) it was thought that a substantial proportion of parasitized individuals might escape detection by the method. In order to investigate this possibility, a special survey was made, by examining 968 people of Bel?m, State of Par?, using both the thick smear of blood taken from 7 to 9:30 p.m. and Knott?s concentration method, with 2cc of blood collected from 11:30p.m. to 3a.m. The assumption had previously been that, by using a concentration method with blood collected during the period of maximum microfilaraemia, practically 100% of the positives would be detected, and the comparison of the results obtained by the two methods would give the error to be expected when using only the first one in general surveys. The results were as follows: N? % People examined . 968 - Total positives . 139 14.3 Positives by the thick smear of blood, collected from 7 to 9:30p.m. 121 12.3 Positives by Knott?s, with 2cc of blood taken from 11:30p.m. to 3a.m. 139 14.3 As shown above, Knott?s technique made with blood collected in late hours of the night revealed only 2% more positives than the thick smear of blood taken from 7 to 9:30p.m. The difference between the percentages of positives obtained by the two methods is not statistically significant. Thence, the examination of thick smears of blood collected at the beginning of the night seems to be sufficient for surveys of Bancrofti?s filariasis in areas where the microfilariae show nocturnal periodicity, since it yields fairly good results and is much more practical than taking slides in late hours, or using other methods which involve the collection of venous blood.